Eksistensi Hospital by Law Pasca UndangUndang 17 Tahun 2023 Tentang Kesehatan - Gustafianof, Gustafianof (CAPITAN: Constitutional Law & Administrative Law Review, 2025)
Another change in the administration of hospitals today is the development of the function of hospitals, which previously only provided health services, to become broader based on Law Number 17 of 2023 concerning Health. Article 197 of the Health Law provides for the expansion of health human resources into Medical Personnel, Health Personnel and Health Support or Support Personnel. The addition of health human resources in the form of Supporting Personnel or Health Support can be interpreted as part of encouraging the implementation of the development of hospital functions as intended in Article 184 paragraph (3) of the Health Law. The presence of non-medical health human resources (medical personnel and health workers) will strengthen the function of hospitals now and in the future. Through normative legal research and approaches to written legislation, and other written legal materials, the results were obtained that the preparation of hospital bylaws does not only contain corporate bylaws and medical staff bylaws, but must also be adapted to developments in the orientation, function and form of hospital services after the enactment of the Health Law.